MEDIATION OF WORK-LIFE BALANCE IN THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP AND DIGITAL LITERACY ON JOB SATISFACTION - Sitompul, Grace Orlyn (Faculty of Economics and Business Universitas Pelita Harapan, 2024)
The primary objective of this study was to explore the influence of transformational leadership and digital literacy on job satisfaction, mediated by work-life balance. Specifically, the research aimed to understand how transformational leadership could affect employees’ perceptions of their work-life balance and digital literacy, and how these perceptions, in turn, influence their overall job satisfaction. The study involved a sample of 101 employees working in the textile industry in Bandung, Indonesia. The observation period for this study was set at one month. Data was analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) to assess both the measurement model (outer model) and the structural model (inner model). The findings of the study reveal: 1) Transformational Leadership had a significant impact on Work-Life Balance. 2) Digital Literacy significantly influenced Work-Life Balance. 3) Work-Life Balance had a significant effect on Job Satisfaction, confirming that employees who manage to balance their personal and professional lives tend to be more satisfied with their jobs. 4) Transformational Leadership does not significantly impact Job Satisfaction through Work-Life Balance. 5) The impact of Digital Literacy on Job Satisfaction was significantly mediated by Work-Life Balance, underscoring strong digital skills may contribute to job satisfaction by enabling individuals to maintain a healthier balance between their work and personal lives. These findings suggest that transformational leadership in the textile industry should focus more on culture changes that support work-life balance and effectively integrate digital literacy. Such an approach can enhance job satisfaction, potentially leading to higher productivity and employee retention.